Performance Audit on Implementation of Drugs and Cosmemtics Act in West Bengal (2012-2017) - CAG of India (CAG of India)
The Government of India (GoI) had enacted the Drugs & Cosmetics Act, 1940 followed by the Drugs & Cosmetics (D & C) Rules, 1945 to regulate manufacture, distribution and sale of drugs and cosmetics in the country. These were applicable to Allopathic, Homeopathic, Unani and Siddha drugs as well as other health related items. The Government of West Bengal established (1965) the Directorate of Drug Control (DDC) under the Health & Family Welfare (H&FW) Department for enforcement of the aforesaid Act and Rules. The DDC was mandated with licensing and inspections of manufacturing units, blood banks and sales premises, approval of formulations of drug for manufacture, drawal and testing of drugs samples for monitoring quality standards and initiating prosecution against offenders. A Performance Audit covering the period from 2012-13 to 2016-17 showed the following shortcomings: 1. The activities of drug control in the State were adversely affected by acute shortage in the cadre of Drug Inspectors as well as infrastructural and manpower shortcomings in the West Bengal State Drug Control and Research Laboratory (SDCRL). Inspections and sampling was meagre to effectively combat the sale of ‘Not of Standard Quality (NSQ)’/ spurious drugs. 2. Significant number of manufacturers/ sellers continued to be in the drug business without valid licences. 3. The test results of the Laboratory were doubtful as it often did not run all the mandatory tests on the samples. There was also delay in generation of test results by the laboratory by which time the NSQ drugs had been consumed by the patients. The Department was unable to create adequate deterrence against NSQ/ spurious drugs owing to inaction on cases reported to be NSQ and the inability to further the prosecution orders. Thus, consumers in the State remained exposed to serious health hazards from spurious and not of standard quality drugs.
Forthe Period 2012-2017